Sudden Visual Impairment In Sellar Region Tumor: A Case Of Pituitary Apoplexy - Anindita Wicitra; Syntia Nusanti; M Sidik (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2020)
Objective : Pituitary apoplexy described as an acute hemorrhagic infarction of the pituitary adenoma causing sudden increase of intra sellar pressure. This condition is a life-threatening disease. The purpose of this article is to report about clinical symptom and methods to diagnose pituitary apoplexy. Methods : A case presentation Result : A 40 y.o male came with a complain of blurry vision since 1 year. Two months before admission, he felt sudden worsening of his visual acuity. He went to private hospital and there was bleeding in his brain CT scan. His right eye visual acuity was 1/300 and his left best visual acuity was 6/12. Relative afferent pupillary defect was positive in the right eye. In funduscopic examination, both of optic nerve head were atrophy. Left eye visual field examination revealed temporal hemianopsia. Cerebral MRI showed a hyper intense lesion on both T1WI and T2WI sequence in sellar region that extends into supra sellar region with sign of sellar floor ballooning. The result of MRI contrast was relatively same and the hormonal exam result was within normal limit. Then he was scheduled for removal tumor surgery from neurosurgery departement. Conclusion : Pituitary apoplexy is a severe clinical syndrome and life-threatening disease. To rule out other disease presenting related symptoms, many ancillary examinations are require to be performed. The treatment of pituitary apoplexy, whether to treat surgically or conservatively, should be made by experts from a multidisciplinary team.